PENGARUH PENDAPATAN DAN PENGELOLAAN KEUANGAN TERHADAP KESEJAHTERAAN BURUH TANI KELAPA SAWIT DI DESA WAJOK HILIR - HAQ, RAHMAD IZUL; Asriati, Nuraini; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The three factors that affect the welfare of oil palm farm workers in Wajok Hilir Village are examined in this study: 1) the impact of income; 2) the impact of financial management; and 3) the combined impact of income and management. This study uses a quantitative approach and cause-and-effect research to examine three variables: income (X1), financial management (X2), and the welfare of oil palm farm employees (Y). In Wajok Hilir Village, 94 oil palm farm employees participated in the study. straightforward random sampling method. Multiple linear regression is used in data analysis. t test partial results: 1) Farmworkers' welfare (Y) is partially influenced by income (X1), with a significance level of 0.012 to 0.05 or a calculated t value t table of 2.567 to 1.993. 2) The welfare of farm workers (Y) is partially influenced by financial management (X2) with a sig value of 0.004 0.05 or a calculated t value t table, namely 3.006 1.993. The results of the simultaneous F test had a significance value of 0.000 0, 05 or a calculated F value F table, namely 9.520 3.12. This demonstrates how the welfare of agricultural employees (Y) is simultaneously influenced by income (X1) and financial management (X2).